Synthesis of homogeneous la0.8Sr0.2CrO3 powders using an ultrasonic spray pyrolysis method - Kim, C.-S.; Hwang, S.I.; Kim, S.W. (Korean Ceramic Society, 2007)
A process to synthesize La0.8Sr0.2CrO3 (LSC), which is a promising material for use as a separator in a soild oxide fuel cell, is investigated in this study. LSC powders without secondary phases could be synthesized with ultrasonic spray pyrolysis and a heat treatment at 1200°C for 20 h: however, it showed an average diameter of 0.6 μm with a wide particle size distribution. On the other hand, LSC powders synthesized with spray pyrolysis at 800°C, heat-treated at 900°C for 5 h, ball-milled and finally heat-treated again at 1200°C for 20 h showed a smaller average diameter of 0.3 μm and narrower size distribution. Very few particles above 0.5 μm were found. Thus, a proper combination of the heat treatment and milling process after spray pyrolysis it determined to be very important in synthesizing fine and uniform LSC perovskite powders.